1988
DOI: 10.1111/j.1570-7458.1988.tb01167.x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance in the wild crop relatives Avena macrostachya and Hordeum bogdani to the aphid Rhopalosiphum padi

Abstract: In previous screening tests the two wild crop relatives Avena macrostachya (Bal., ex Coss. et Dur.) and Hordeum bogdani (Wil.) demonstrated a high degree of resistance to the aphid Rhopalosiphum padi (L.). In a choice situation using wild and cultivated oats and barley, alate aphids settled in lower numbers on the wild species. The results were, however, variable in the Avena combination. Nymph production was significantly higher, development time shorter and adult weight higher on the cultivated varieties. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
3
7
0
Order By: Relevance
“…The primary nutritional challenge faced by aphids is the acquisition of nitrogen from phloem sap in the form of amino acids (Terra 1988). Nitrogen fertilization of a variety of grasses tends to increase the amount and alter the composition of amino acids in phloem, which can, in turn, increase aphid population growth rates (Weibull 1988, Fraser and Grime 1999, Isopp et al 2000. Thus, our result that N fertilization increased plant biomass, tissue %N, and aphid fecundity is concordant with many previous studies (see review in Awmack and Leather 2002).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The primary nutritional challenge faced by aphids is the acquisition of nitrogen from phloem sap in the form of amino acids (Terra 1988). Nitrogen fertilization of a variety of grasses tends to increase the amount and alter the composition of amino acids in phloem, which can, in turn, increase aphid population growth rates (Weibull 1988, Fraser and Grime 1999, Isopp et al 2000. Thus, our result that N fertilization increased plant biomass, tissue %N, and aphid fecundity is concordant with many previous studies (see review in Awmack and Leather 2002).…”
Section: Discussionsupporting
confidence: 92%
“…This result mirrors field choice tests in which R. padi aphids preferentially colonized the plant species on which they had higher fecundity (Weibull 1988). This result mirrors field choice tests in which R. padi aphids preferentially colonized the plant species on which they had higher fecundity (Weibull 1988).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The amino acid composition of the phloem has also been related with aphid host plant resistance. Studies in cereal crops including oats, barley, rice, and wheat have shown that speciÞc amino acids are correlated with resistance to aphids (Weibull 1988(Weibull , 1994Kazemi and Van Emden 1992). Studies in legumes like Vicia faba L. (Holt and Birch 1984) and Pisum sativum (Auclair 1976) suggest a potential role for total content of free amino acids and amino acids composition in aphid resistance.…”
mentioning
confidence: 97%
“…Srivastava et al (1983) found that alanine and γ-aminobutyric acid stimulated feeding behavior in pea aphid, Acyrthosiphon pisum (Harris) (Hemiptera: Aphididae), whereas as several amino acids such as asparagine, cysteine, proline and tyrosine deterred feeding behavior. Amino acid composition has been linked to resistance to aphid species in cereal crops (Weibull, 1988(Weibull, , 1994. Aphids, due to their ability to pierce directly into a phloem sieve element, are able to get to a richer source of nitrogen as compared to chewing herbivores; most of the nitrogen within a plant is associated with defensive compounds and other, unusable maters.…”
Section: Introductionmentioning
confidence: 99%